"Armed with Glamour and Collection Tins": Femininity and Voluntary Work in Wartime South Australia, 1939–45. (November 2019) - Harris, Rachel
Abstract : Between 1939 and 1945, more than 500 voluntary organisations operated across South Australia, the largest with a membership of more than 30, 000 women. Focusing on the voluntary activities of these South Australian women – which ranged from providing material comforts for servicemen to fundraising as participants in beauty and pin-up competitions – this article reveals that female voluntarism was a highly visible and ubiquitous part of the home front experience in Australia during World War II. Oral histories, press reports and archival sources show that female voluntary work was considered crucial to the upkeep of male morale, and thus functioned to ease concerns regarding the war's impact on traditional gender relations. In practice, however, the close relationship between paid and unpaid work meant voluntarism did not necessarily limit the wartime gains of South Australian women. Instead the rhetoric used to describe women's voluntary work obscured the social and economic benefits it often provided.